2011
DOI: 10.1158/1055-9965.epi-11-0531
|View full text |Cite
|
Sign up to set email alerts
|

Measured Body Mass Index in Adolescence and the Incidence of Colorectal Cancer in a Cohort of 1.1 Million Males

Abstract: Background and Aims: The increasing prevalence of adolescent obesity affects adult health. We investigated the association of adolescent overweight with colorectal cancer incidence in a large cohort of males.Methods: Body mass index (BMI) was measured in 1.1 million Jewish Israeli males who underwent a general health examination at ages 16 to 19 between 1967 and 2005. Overweight was defined as BMI ! 85th percentile of the standard U.S. distribution in adolescence. Colorectal cancer was identified by linkage wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 34 publications
(37 reference statements)
1
43
2
1
Order By: Relevance
“…We speculated the differences in pathophysiology of type 2 diabetes in Asian individuals versus European individuals may contribute to it. For example, it has been demonstrated that the incidence of diabetes in Asia is less strongly associated with overweight than in Europe [39], and overweight is substantially associated with colon cancer incidence in adults [40].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated the differences in pathophysiology of type 2 diabetes in Asian individuals versus European individuals may contribute to it. For example, it has been demonstrated that the incidence of diabetes in Asia is less strongly associated with overweight than in Europe [39], and overweight is substantially associated with colon cancer incidence in adults [40].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between obesity and carcinogenesis is well known (16,(18)(19)(20). Number and size of adenomas were found to correlate with visceral fat accumulation (21).…”
Section: Discussionmentioning
confidence: 98%
“…However, most prior studies have relied on self-reported recall of early-life weight6 7 14–16 or have been limited by small numbers of events 4 5 8 9 12 13. To date, few large studies have addressed this question using measured adolescent BMI, and these studies indicate a strong association between adolescent BMI and CRC 10 11. In a study of Israeli male conscripts followed for CRC for approximately 18 years, men with BMI in the top quintile experienced 69% higher risk of colon cancer than men in the lowest quintile (HR 1.69; 95% CI 1.24 to 2.29) 11.…”
Section: Discussionmentioning
confidence: 99%